Search for heavy resonances decaying to tau lepton pairs in proton-proton collisions at root s=13 TeV - Ruiz Vargas, J. C.; Battilana, C.; Malberti, M.; Pigazzini, S.; Nardo, G. De; Thyssen, F.; Zanetti, M.; Fedi, G.; Giassi, A.; Grippo, M. T.; Ligabue, F.; Lomtadze, T.; et al. (Springer, 2017)
A search for heavy resonances that decay to tau lepton pairs is performed using proton-proton collisions at root s = 13 TeV. The data were collected with the CMS detector at the CERN LHC and correspond to an integrated luminosity of 2.2 fb(-1). The observations are in agreement with standard model predictions. An upper limit at 95% confidence level on the product of the production cross section and branching fraction into tau lepton pairs is calculated as a function of the resonance mass. For the sequential standard model, the presence of Z' bosons decaying into tau lepton pairs is excluded for Z/ masses below 2.1 TeV, extending previous limits for this final state. For the topcolor-assisted technicolor model, which predicts Z' bosons that preferentially couple to third-generation fermions, Z' masses below 1.7 TeV are excluded, representing the most stringent limit to date.
Keywords: Beyond Standard Model; Hadron-Hadron scattering (experiments); Particle and resonance production